Pelatihan Sistem Digital dan Komunikasi Menggunakan Modul Arduino pada Sekolah Menengah Kejuruan - Fathur Zaini Rachman; Nurwahidah Jamal; Nur Yanti; Qory Hidayati (Abdimas Universal, 2019)
The aim of the activity is to increase the competence of teachers and students by training Arduino-based practice modules in the implementation of digital and communication systems that have multi-input and multi-output devices. Partner problems are industry technology 4.0 and teacher competence. Industry 4.0 technology issues are implemented in practical training modules that are useful as learning media that can be implemented for various applications. The problem of teacher competence with training and development of learning media so as to be able to create and innovate in digital and communication systems. The method used in this activity is discussion, explanation, demonstration, exercise, and observation. The results of this activity increase the competence and knowledge of vocational schools by marked the participants are able to operate and implement modules.